An Analysis of Authentic Assessment Implementation Based on Curriculum 2013 in SMP Negeri 4 Singaraja - Suarimbawa, Kadek Agus; Marhaeni, A. A. I. N.; Suprianti, GAP (LPPM Undiksha, 2017)
This research aimed at (1) describing authentic assessment preparation according to Curriculum 2013 by grade seven teachers in SMP Negeri 4 Singaraja, (2) describing authentic assessment implementation according to Curriculum 2013 (3) describing obstacles experienced by teachers in implementing authentic assessment according to Curriculum 2013 This research is descriptive qualitative study. The data were gaining by study documents, observations, and interview. The result shows that (1) the conformity of authentic assessment preparation based on Curriculum 2013 by the teachers in is 53.97% which category is sufficient. (2) Conformity of authentic assessment implementations by the teachers is 44.4% which category is sufficient. (3) Obstacles experienced by teachers are in terms of students’ number and lack of time in the authentic assessments implementation. In conclusion, authentic assessments implementation already measured the competence of knowledge, attitudes and skills of the students according to Curriculum 2013.